2022
DOI: 10.1155/2022/6887192
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs from Plasma Extracellular Vesicles Are Signatory Noninvasive Prognostic Biomarkers against Atherosclerosis in LDLr-/-Mice

Abstract: Circular microRNAs (miRNAs) have become central in pathophysiological conditions of atherosclerosis (AS). However, the biomarkers for diagnosis and therapeutics against AS are still unclear. The atherosclerosis models in low-density lipoprotein receptor deficiency (LDLr-/-) mice were established with a high-fat diet (HFD). The extraction kit isolated extracellular vesicles from plasma. Total RNAs were extracted from LDLr-/- mice in plasma extracellular vesicles. Significantly varying miRNAs were detected by em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies have shown that miRNAs selectively delivered by ectosomes mediate the pathological processes of a variety of diseases, and disease progression can be effectively delayed through drug delivery systems using ectosomes as carriers [ 40 ]. MiR-350-3p was found to be present in intracellular and extracellular vesicles in plasma, and may be involved in the regulation of atherosclerosis, indicating that miR-350-3p can be transferred into EVs and participate in some pathological processes [ 41 ]. Through miRNA sequencing and analysis of ectosomes from macrophages stimulated by mechanical loading, we found that miR-350-3p was significantly increased in stimulated ectosomes, and increased miR-350-3p expression was also detected in chondrocytes co-cultured with these ectosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miRNAs selectively delivered by ectosomes mediate the pathological processes of a variety of diseases, and disease progression can be effectively delayed through drug delivery systems using ectosomes as carriers [ 40 ]. MiR-350-3p was found to be present in intracellular and extracellular vesicles in plasma, and may be involved in the regulation of atherosclerosis, indicating that miR-350-3p can be transferred into EVs and participate in some pathological processes [ 41 ]. Through miRNA sequencing and analysis of ectosomes from macrophages stimulated by mechanical loading, we found that miR-350-3p was significantly increased in stimulated ectosomes, and increased miR-350-3p expression was also detected in chondrocytes co-cultured with these ectosomes.…”
Section: Discussionmentioning
confidence: 99%